Cláusulas antielusivas específicas y capacidad contributiva: a propósito de la limitación a la deducción de intereses - Otoya Cabrera, Jorge (2021)
In this article, the author develops the change of focus in the rules for the deduction of interest as a consequence of the regulatory change that occurred in 2019 with regard to the application of the anti tax avoidance law as well as its application in Peru as of 2021.